DIVERSION AND TRANSFORMATION OF POLICY RESOURCES (SOCIAL AUDIT STUDY ON IMPLEMENTATION OF MASBAGIK TRADITIONAL MARKET RELOCATION) - Sukmayeti, Evi (Universitas Muhammadiyah Yogyakarta, 2018)
The revitalization of Pasar Lama Masbagik is a strategic policy of the Government of East Lombok Regency Local Government in 2015 funded by a loan to the Government Investment Center. By relocating traders from the Old Market to Modern Market, as well as expanding and renovating the Old Market for potential new investors, the government hopes to optimize the local assets with supporting transaction convenience for the buyer. However, the policy is considered to be detrimental economically by target groups that are in fact local people, followed by a series of rejections. The policy began to be implemented in 2016. The models and approaches in public policy analysis in academic field have been using a common methodology. The availability of applied literature has not been generated in academic research. The study of the policy implementation, using a social auditing approach that gives reference to how the 'black box' implementation runs in the path as well as with a bias (diversion and transformation). Data collection was performed by purposive method and snowball sampling to stakeholders. Document tracking supported in informants determination being the way of triangulating data in addition to observation. The revitalization of the old traditional Masbagik market involves the action of relocating traders to Pasar Masbagik Baru and residents who live around the market area toward new residence. The process of policy implementation precisely run on the target of time. Meanwhile, the allocation of material resources such as lapak, kiosk, land and financial compensation for the sufferer groups who are traders and residents met some biases (diversion and transformation). Biases caused some target groups to be suffered or being unexpected beneficiaries by relocation.